Interstate Disparity in Combating COVID-19 in India: Efficiency Estimate Across States - Maity, Shrabanti; Sinha, Anup (Journal of Health Management, 2024)
Currently, COVID-19 is the most lethal menace in the world. Due to its health and economic consequences, it becomes a serious challenge for the economy. The present article aims to explore India's interstate disparities of efficiency in combating COVID-19 based on secondary data. Besides, an attempt has been made to pinpoint the factors responsible for the inefficiency of resisting this deadly virus. The interstate efficiency measurement is facilitated by applying stochastic production frontier analysis. The empirical result divulges that among the Indian states, Bihar is the most efficient in combating COVID-19. The empirical estimation of the frontier model discloses that the number of doctors, nurses, police force, isolation beds and hotspots positively and significantly influence the recovery rate from COVID-19 in Indian states. The empirical results of the inefficiency effects model suggest that the share of elderly and urbanisation reversely influence the efficiency in combating the virus, while favourable sex ratio, literacy rate, regular salaried employment, digitalisation and ruralisation stimulate the efficiency of the concerned state. The study concludes that efficient utilisation, coupled with the advancement of the existing health infrastructure, is imperative for the acceleration of the recovery rate from this pandemic.
Keywords: Health and Economic Consequences; Health Infrastructure; Novel Coronavirus; COVID-19